Re‐transplantation in pediatric patients with failure of primary transplant due to recurrent focal segmental glomerulosclerosis: A pediatric nephrology research consortium study. (11th July 2021) - Maniar, Aesha; Hooper, David K.; Sethna, Christine B.; Singer, Pamela; Traum, Avram; Benoit, Elizabeth; Kotzen, Elizabeth; Verghese, Priya; Garro, Rouba; Kamel, Margaret; Ranch, Daniel; Shih, Weiwen; et al.
Abstract: Introduction: Recurrent focal and segmental glomerulosclerosis (FSGS) in kidney transplant recipients is associated with lower graft survival and increased morbidity. There are limited data to guide the decision to re‐transplant patients with transplant failure due to FSGS recurrence. We aimed to evaluate outcomes in patients re‐transplanted after having initial graft failure due to recurrent FSGS and to study physician attitudes and practice patterns. Methods: Retrospective data from 10 centers were collected on 20 patients transplanted between January 1997 and September 2018. A survey was sent to nephrologist members of the Pediatric Nephrology Research Consortium. Results: Mean patient age (years) was 9.8 ± 4.8 at first transplant and 15.9 ± 4.9 at re‐transplantation. Pre‐transplant plasmapheresis was used in 1 (5.3%) primary transplant vs. 7 (38.9%) re‐transplants ( p  = .03). Nephrotic syndrome recurred in 14 patients (70%) after re‐transplantation and was severe in 21.1% vs. 64.7% after first transplant ( p  = .04). Graft survival was significantly higher in the second transplant (p .009) with 70% having functioning grafts at a median of 25.2 months. Thirty‐one physicians from 21 centers completed the survey, 94% indicated they would re‐transplant such patients, 44.4% preferred a minimum waiting period before re‐transplantation, 36.4% preferred living donors, and 22.2% indicated having protocols for re‐transplantation at their centers. Conclusions: Consideration for re‐transplantation is high among pediatric nephrologists. Pre‐transplant plasmapheresis was more frequent in re‐transplanted patients. Nephrotic syndrome recurrence was less severe, with better graft survival. More data and a larger population are necessary to further evaluate outcome determinants and best practices in this special population.